Case Report: Biological treatment of epidermolysis bullosa acquisita: report on four cases and literature review - Szymański, Konrad; Kowalewski, Cezary; Pietrzyk, Ewelina; Woźniak, Katarzyna (Frontiers in Immunology, 2023)
Epidermolysis bullosa acquisita (EBA) is a chronic autoimmune subepidermal bullous disease characterized by the presence of autoantibodies targeting type VII collagen, an antigen in the basement membrane zone. This leads to the formation of blisters on the skin and mucous membranes.Standard therapy for EBA includes a combination of systemic corticosteroids and dapsone, however, severe cases may require advanced biological treatment. The article reports on four cases of EBA successfully treated with infliximab, rituximab (Rtx) and/or intravenous immunoglobulin (IVIG).Case 1: a 72-year-old female suffering from severe EBA for 8 years. Standard therapy with prednisone and dapsone did not control EBA and caused relevant side effects. Due to Rtx therapy (2x1 g i.v.), EBA has been controlled and it has been possible to reduce maintenance treatment to dapsone 50 mg/day. Case 2: a 53-year-old female with 10 year-long history of EBA previously treated with prednisone and dapsone, colchicine, tetracycline, mycophenolate mofetil, and sulfasalazine was infused with IVIG (6 x 2 g/kg b.w.) achieving partial remission maintained without systemic therapy.Case 3: a 29-year-old male suffering from EBA for 7 years. Due to the lack of disease control by a combination of prednisone and dapsone nor mycophenolate mofetil, and the development of corticosteroid-related massive stretch marks was initially administrated with IVIG (8x2 g/kg b.w.), resulting in only partial control of the disease. Consequently, he received Rtx (2x1g), which resulted in satisfactory disease control while reducing the methylprednisolone dose to 4 mg/day. Case 4: a 25-year-old male dealing with Crohn's disease for 7 years and EBA for 6 years has achieved remission of both diseases after therapy with infliximab (12x350 mg).